Characterization and optimization of mnn11Δ-mediated enhancement in heterologous protein production in Kluyveromyces marxianus - Shihao Zhou; Pingping Wu; Haiyan Ren; Jungang Zhou; Yao Yu; Hong Lu (Microbial Cell Factories)
Abstract Background N-glycosylation is a prevalent post-translational modification in eukaryotes, essential for regulating protein secretion. In Saccharomyces cerevisiae, glycosylation mutants have been shown to enhance the secretion of heterologous glycosylated proteins. However, whether these mutants can also increase the secretion of non-glycosylated proteins and whether the growth defects associated with glycosylation mutations can be mitigated remains unclear. This study aimed to characterize and optimize enhanced secretory expression in the promising yeast host Kluyveromyces marxianus by deleting MNN11, which encodes a subunit of the mannose polymerase II complex responsible for elongating α-1,6-linked mannose chains. Results Compared to wild-type cells, the mnn11Δ cells significantly increased the secretion activities of four glycosylated enzymes and three non-glycosylated enzymes in flasks, with increases ranging from 29 to 668%. Transcriptomic analysis of mnn11Δ mutant revealed upregulation of genes related to essential protein secretion processes, including vesicle coating and tethering, protein folding, translocation, and glycosylation. Additionally, genes involved in vacuolar amino acid transport and amino acid biosynthesis were upregulated, suggesting an amino acid shortage, which might contribute to the observed severe growth defect of the mnn11Δ mutant in a synthetic medium with inorganic nitrogen. Supplementation of the synthetic medium with amino acids or low concentrations of yeast extract alleviated this growth defect, reducing the specific growth rate difference between wild-type strain and mnn11Δ cells from 65% to as little as 2%. During high-density fermentation, the addition of 0.5% yeast extract substantially reduced the lag phase of mnn11Δ mutants and increased the secretory activities of α-galactosidase, endoxylanase, and β-glucanase, by 11%, 18%, and 36%, respectively, compared to mnn11Δ mutant grown without yeast extract. Conclusion In K. marxianus, deletion of MNN11 enhances the secretion of both glycosylated and non-glycosylated proteins by improving key protein secretion processes. The growth defect in the mnn11Δ mutant is closely tied to insufficient amino acid supply. Supplementing the synthetic medium with low concentrations of organic nitrogen sources effectively alleviates this growth defect and enhances secretory expression. This strategy could be applied to optimize the expression of other glycosylation mutants.